2019
DOI: 10.1080/10438599.2019.1629533
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and productivity in family firms: evidence from a sample of European firms

Abstract: This paper estimates the impact of R&D investments on the productivity of European family firms. For the period 2007-2009, we consider a Cobb-Douglas production function augmented by R&D intensity. Specifically, we address the questions of whether the R&D returns of family firms differ from that of non-family firms. Final outcomes suggest that, on average, non-family firms conducting R&D record a productivity gain of about 5-8 % compared to non-innovative firms. Additionally, the innovative family firms are ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 140 publications
3
9
1
2
Order By: Relevance
“…Hult, Hurley, and Knight (2004, p. 429) claim that information used in innovation enhances the control and competence of the management over processes. Thus, the efficiency and effectiveness of the organization improves (Aiello, Mannarino, & Pupo, 2019;Kijek & Kijek, 2019;Rajapathirana & Hui, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Hult, Hurley, and Knight (2004, p. 429) claim that information used in innovation enhances the control and competence of the management over processes. Thus, the efficiency and effectiveness of the organization improves (Aiello, Mannarino, & Pupo, 2019;Kijek & Kijek, 2019;Rajapathirana & Hui, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, although their higher flexibility and their longer‐term perspective would be in itself factors conducive to innovation, FFs are less willing to innovate due to their risk aversion, lack of resources and knowledge, and reluctance to ask for external financial investments (Aiello, Cardamone, et al, 2020). Additionally, some studies highlighted that FFs achieve higher innovation outputs compared with non‐family firms (Duran et al, 2016), whereas others found that the returns to their R&D investments are low (Aiello, Mannarino, & Pupo, 2020).…”
Section: Family Businesses Csr and Eco‐innovation: Literature Reviewmentioning
confidence: 99%
“…Other research studies (Chen and Hsu, 2009;Munoz-Bullon and Sanchez-Bueno, 2011) assert that family firms invest in R&D but not as much as non-family ones. Aiello et al (2020) stated that the R&D returns of innovative efforts for family firms are less than non-family ones. The pioneers of agency theory (Jensen and Meckling, 1976) assert that agency costs are less in family firms, as there are emotional ties among business members.…”
Section: Hypotheses Developmentmentioning
confidence: 99%